Implementation of Promotional Strategies for Pondok Pesantren Darul Ilmi Wal Amal Through the Use of Media Flyer - Sumarni, Neni; Fajrin, Yeni; Arisandi, Vidya (Institut Teknologi dan Bisnis Asia Malang, 2025)
Purpose: The organization of this community service activity aims to enhance public awareness of Pondok Pesantren DIWA, improve the reputation of Pondok Pesantren DIWA, and attract community interest in enrolling their children to study religious knowledge at Pondok Pesantren DIWA. Method: The methods employed in this community service initiative are implementation-based, involving guidance and the creation of promotional flyers for Pondok Pesantren DIWA, along with the application of these promotions through social media (online) and direct dissemination (offline). Promotional fliers are created using the Canva application. Practical Application: The community service activities are conducted through direct guidance and training in the creation of promotional fliers using the Canva application, which is relatively easy to use for anyone. Comprehensive promotion is essential to achieve the desired objectives effectively, with flyer media serving as one of the methods used by the pesantren to disseminate information about itself to all segments of society. Conclusion: The outcome of this service activity includes the production of promotional fliers, which are disseminated via Instagram and through direct outreach to target markets or community members known as offline promotion.